Kontribusi mahasiswa dalam meningkatkan kualitas sumber daya manusia dan mewujudkan visi Indonesia Emas 2045 - Soleh, Noris; Fajriah, Fajriah; Rahman, Fadali (Nur Science Institute, 2024)
Indonesia Emas 2045 is a grand vision to make Indonesia a developed country by 2045, after 100 years of independence. Achieving this vision requires contributions from all elements of the nation, including students as the next generation. The purpose of this study is to explore and analyze the strategic role that students can play in realizing the vision of Indonesia Emas 2045. The analysis approach uses qualitative description. The results show that students play an essential role in improving the quality of human resources through quality education, mastery of science, and involvement in research and development. They can also become agents of change by developing innovations in technology, economy, society, and culture and act as young entrepreneurs who create new jobs. In addition, students play a role in strengthening character and nationalism by upholding the values ​​of Pancasila and preserving the nation's culture. Active participation in national development through involvement in decision-making and various social, political, and economic activities is also crucial. By building networks and partnerships at home and abroad, students can support Indonesia's progress and promote the nation's potential at the global level.